Tourism Management: Antecedents of Tourism Sharing Behavior, Visitor Satisfaction as Mediate - Suwitho, Suwitho; Triyonowati, Triyonowati; Mustika, Hindah; Pradhani, Fastha Aulia (International Journal of Social Science and Business, 2024)
The tourism sector in East Java can increase economic growth, so it must be maintained and further enhanced to be able to create new business opportunities, places to learn history, culture, and other positive values. This study aims to explore the impact of visitor satisfaction on tourist attractions in East Java, focusing on factors that influence tourism sharing behavior. The sample of this study was obtained as many as 100 respondents. The analysis method used is Structural Equation Modeling Partial Least Squares (SEM PLS 3.0). The study found that cultural attractions had no effect on tourism sharing behavior, and general attractions had no effect on tourism sharing behavior. Cultural attractions affect visitor satisfaction (Tourist), public attractions affect visitor satisfaction (Tourist), and visitor satisfaction (Tourist) is able to mediate a strong influence between variations in variables of General Attraction and Cultural Attractions on Tourism sharing behavior. The findings of this study prove that when travelers feel satisfied with the attractions displayed, they will share with others in their community. The implication of these findings is the importance of paying attention to visitor satisfaction factors in the management of tourist attractions, as well as considering cultural and general attractions as important factors in improving the tourist experience in East Java.